Kinesin Kif3b mutation reduces NMDAR subunit NR2A trafficking and causes schizophrenia‐like phenotypes in mice. (20th November 2019) - Alsabban, Ashwaq Hassan; Morikawa, Momo; Tanaka, Yosuke; Takei, Yosuke; Hirokawa, Nobutaka
Abstract: The transport of N ‐methyl‐d ‐aspartate receptors (NMDARs) is crucial for neuronal plasticity and synapse formation. Here, we show that KIF3B, a member of the kinesin superfamily proteins (KIFs), supports the transport of vesicles simultaneously containing NMDAR subunit 2A (NR2A) and the adenomatous polyposis coli (APC) complex. Kif3b +/− neurons exhibited a reduction in dendritic levels of both NR2A and NR2B due to the impaired transport of NR2A and increased degradation of NR2B. In Kif3b +/− hippocampal slices, electrophysiological NMDAR response was found decreased and synaptic plasticity was disrupted, which corresponded to a common feature of schizophrenia (SCZ). The histological features of Kif3b +/− mouse brain also mimicked SCZ features, and Kif3b +/− mice exhibited behavioral defects in prepulse inhibition (PPI), social interest, and cognitive flexibility. Indeed, a mutation of KIF3B was specifically identified in human SCZ patients, which was revealed to be functionally defective in a rescue experiment. Therefore, we propose that KIF3B transports NR2A/APC complex and that its dysfunction is responsible for SCZ pathogenesis. Synopsis: Altered synaptic surface expression of N ‐methyl‐d ‐aspartate receptors (NMDARs) affects neuronal function and has been linked to schizophrenia. Here, the kinesin KIF3B is shown to transport NMDAR subunit 2A (NR2A) into neuronal dendrites, with its disruption causing schizophrenia‐like phenotypes in mice. Kif3b +/− mice exhibit schizophrenia‐like behavioral phenotypes. KIF3B transports vesicles containing the NR2A complex into neuronal dendrites. A mutation in human Kif3b gene was identified in schizophrenia patients. The patient mutation‐carrying KIF3B is functionally defective and cannot rescue Kif3b +/− phenotypes. Abstract : Simultaneous vesicular transport of NMDAR subunit 2A and the adenomatous polyposis coli (APC) complex in neuronal dendrites depends on Kif3b and is disrupted by schizophrenia‐linked mutations.